Predictors and incidence of post-partum depression: a longitudinal cohort study - Abdollahi, Fatemeh; Zarghami, Mehran; Azhar, Md Zain; Shariff Ghazali, Sazlina; Lye, Munn Sann (Wiley-Blackwell Publishing Asia, 2014)
AIM: This study was designed to identify the incidence and the related factors contributing to post-partum depression (PPD) in women in Iran for the first time. MATERIAL AND METHODS: A total of 2279 eligible pregnant women from 32-42 weeks of pregnancy to 12 weeks post-partum (2009) who attended primary health centers in Mazandaran province were screened for depression using the Iranian version of the Edinburgh Postnatal Depression Scale. Pregnant women free from depression were assessed using validated questionnaires, including the Premenstrual Syndrome Questionnaire, Social Support Appraisal Scale, Network Orientation Scale, General Health Questionnaire, Marital Inventory, Life Events Rating Scale and Parental Expectation Survey. Logistic regression analysis was used to determine the risk factors of PPD. RESULTS: Of 1801 women who screened negative for depression at 32-42 weeks' gestation, cumulative incidence proportions were 6.7%, 4.3% and 4.5% during 0-2, >2-8 and >8-12 weeks post-partum, respectively. The factors predictive of PPD were: history of depression during the first two trimesters of pregnancy (odds ratio [OR] = 2.55, 95% confidence interval [CI] = 1.59-4.1); psychiatric disorder during pregnancy (OR = 1.08, 95%CI = 1.06-1.11); gestational diabetes (OR = 2.93, 95%CI = 1.46-5.88); recurrent urinary infection (OR = 2.25, 95%CI = 1.44-3.52); unwanted pregnancy (OR = 2.5, 95%CI = 1.69-3.7) and low household income (OR = 3.57, 95%CI = 1.49-8.5). The risk was decreased with increasing age (OR = 0.88, 95%CI = 0.84-0.92) and those with high self-efficacy for mothering (OR = 0.7, 95%CI = 0.62-0.78). CONCLUSION: A high rate of new cases of PPD was identified in Iranian women. A combination of psychological, sociological, obstetric and sociodemographic factors can render mothers vulnerable to post-partum depression.